RF and microwave transmitter design - Grebennikov, Andrei 1956 (Wiley series in microwave and optical engineering, 2011)
"RF and Microwave Transmitter Design is unique in its coverage of both historical transmitter design and cutting edge technologies. This text explores the results of well-known and new theoretical analyses, while informing readers of modern radio transmitters' pracitcal designs and their components. Jam-packed with information, this book broadcasts and streamlines the author's considerable experience in RF and microwave design and development"--Provided by publisher